On the occurrence of Bursatella leachii de Blainville, 1817 in Izmir Bay, Turkey - KAZAK, M.; CAVAS, L. (Mediterranean Marine Science, 2007)
One of the well- established alien species in the eastern Mediterranean basin is Bursatella leachii, also known as a lessepsian immigrant. The present paper provides a contribution to Bursatella leachii’sdistribution in the Bay of Izmir, Turkish Aegean Sea.